Loading

QUOTIENT RULE: [u(x) / v(x)]' = [u'(x)v(x) - u(x)v'(x)] / v^{2}We have: u(x) = x^{4} - 1, hence u'(x) = 4x^{3}v(x) = x^{4} + 1, hence v'(x) = 4x^{3}So we have: [(4x^{3})*(x ^{4} + 1) - (4x^{3})*(x

One to one online tution can be a great way to brush up on your Maths knowledge.

Have a Free Meeting with one of our hand picked tutors from the UK’s top universities

Find a tutor

One to one online tution can be a great way to brush up on your Maths knowledge.

Have a Free Meeting with one of our hand picked tutors from the UK’s top universities

Find a tutor